2022
DOI: 10.1002/celc.202101445
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Passivation and Cation Flux at Incipient Solid‐Electrolyte Interphases on Multi‐Layer Graphene using High Resolution Scanning Electrochemical Microscopy

Abstract: The solid electrolyte interphase (SEI) is a dynamic, electronically insulating film that forms on the negative electrode of Li+ batteries (LIBs) and enables ion movement to/from the interface while preventing electrolyte breakdown. However, there is limited comparative understanding of LIB SEIs with respect to those formed on Na+ and K+ electrolytes for emerging battery concepts. We used scanning electrochemical microscopy (SECM) for the in situ interfacial analysis of incipient SEIs in Li+, K+ and Na+ electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…1a and b, which is consistent with other observations. 24,25 The microstructure of SUCN was similar to that of sea urchin, with numerous pointed cone-shaped nanofibers sprouting on its main structure (Fig. 1c and d).…”
Section: Structure Of Samplesmentioning
confidence: 76%
“…1a and b, which is consistent with other observations. 24,25 The microstructure of SUCN was similar to that of sea urchin, with numerous pointed cone-shaped nanofibers sprouting on its main structure (Fig. 1c and d).…”
Section: Structure Of Samplesmentioning
confidence: 76%
“…These curves fit to typical approach curve models (Figure S12) indicating k eff of � 2×10 À 4 cm/s, significantly slower than k eff measured at conductive substrates in aqueous media and in line with measurements at SEI found on Li metal and graphitic electrodes after cycling. [35,36] We emphasize the actual rates are likely slower, but this result clearly suggests the formation of a passivating SEI structure in our 55 mol/kg K(FSA) 0.6 (OTf) 0.4 electrolyte during cycling. Hard x-ray photoelectron spectroscopy measurements in our previous report suggested that various structures deposit on the PTCDI surface after cycling including F-and S-containing components.…”
Section: Methodsmentioning
confidence: 82%
“…It is well-known that the electrolyte composition can impact the formation and properties of the SEI. 1,[57][58][59] To avoid possible alteration of the SEI by the presence of K metal, 60 we utilized graphitekMn-PB full cells. Aer 10 cycles at 0.1C, we quickly disassembled the cells inside a glovebox, rinsed the graphite electrodes using fresh DEC and allowed them to dry in the glovebox.…”
Section: Surface Analysis and Simulationsmentioning
confidence: 99%